Konflik Agraria Pada Tanah Milik Pemerintah di Pinggiran Irigasi Sungai Paring Martapura - Wahdah, Wahdah; Mawaddah, Siti; Bachtiar, Bachtiar; Rico, Muhammad; Syauri, Muhammad Sofian; Sriwati, Sriwati (FACTUM: Jurnal Sejarah dan Pendidikan Sejarah, 2023)
The agrarian conflicts on government-owned land on the outskirts of Irigasi St., Sungai Paring, Martapura, involve many parties. At least three parties were involved in this conflict: small traders, landowners, and the Banjar Regency government. This research describes the background, resolution, and impact of conflicts between landowners and small traders. This research uses qualitative methods, which are described descriptively. The research results show that the conflict started with landowners who felt disturbed by the establishment of small traders’ stalls that covered fish ponds and sports fields. Apart from that, this land is used as a residence, producing household waste, which causes an unpleasant odor. The conflict resolution is carried out outside the court (non-litigation) by negotiating between land owners and small traders who do not find an agreement so that it continues through conciliation. The small trader asked for help from a lawyer for the defense, saying that the warning letter given by the Banjar Regency’s civil service police unit was not following the applicable laws and regulations. Given the case, there are positive and negative impacts. The positive impact is to build public awareness that government-owned land should not be misused for personal interests. Meanwhile, the negative impact of social relations between landlords, small traders, and stall owners becomes less good.